2019
DOI: 10.3390/nano9030462
|View full text |Cite
|
Sign up to set email alerts
|

Poly-ε-Caprolactone/Gelatin Hybrid Electrospun Composite Nanofibrous Mats Containing Ultrasound Assisted Herbal Extract: Antimicrobial and Cell Proliferation Study

Abstract: Electrospun fibers have emerged as promising materials in the field of biomedicine, due to their superior physical and cell supportive properties. In particular, electrospun mats are being developed for advanced wound dressing applications. Such applications require the firers to possess excellent antimicrobial properties in order to inhibit potential microbial colonization from resident and non-resident bacteria. In this study, we have developed Poly-ε-Caprolactone /gelatin hybrid composite mats loaded with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 64 publications
(72 reference statements)
2
42
0
Order By: Relevance
“…4C). Ramalingam et al reported the fibers' diameter for the electrospun PCL/Gel hybrid composite nanfabrous woud dressing which ranged from 150 to 250 nm with an average of 234 ± 52 nm 44 . Ajmal et al studied the electrospun PCL/Gel fibers effect on the full thickness wounds and the fabricated PCL/Gel fibers' mean diameter was 234.1 ± 98.2 nm 45 .…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…4C). Ramalingam et al reported the fibers' diameter for the electrospun PCL/Gel hybrid composite nanfabrous woud dressing which ranged from 150 to 250 nm with an average of 234 ± 52 nm 44 . Ajmal et al studied the electrospun PCL/Gel fibers effect on the full thickness wounds and the fabricated PCL/Gel fibers' mean diameter was 234.1 ± 98.2 nm 45 .…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Electrospun mats (10 × 10 mm) were placed on the swabbed bacterial cultures and incubated at 35 ± 2 °C for 24 h. The antibacterial activity was assessed as a zone of inhibition in millimeters. The bacterial strains such as Staphylococcus aureus , Staphylococcus epidermidis , Pseudomonas aeruginosa , Escherichia coli and methicillin resistant Staphylococcus aureus (MRSA) were used for the study [45].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the in vitro assessment of antibacterial activity of obtained scaffold demonstrated a high antibacterial activity and an inhibitory effect on the growth of both S. aureus and E. coli bacteria (antibacterial activity was dramatically increased, from 36.67 to 100%, after combining Ag nanoparticles with PCL, as compared to constructs without Ag) [ 85 ]. Biocompatible PCL/gelatin hybrid composite mats loaded with natural herbal extract from Gymnema sylvestre plant were prepared by Ramalingam et al in order to prevent bacterial colonization [ 14 ]. The electrospun mats promoted cellular attachment, spreading and proliferation of human primary dermal fibroblasts and cultured keratinocytes, which are crucial parenchymal cell-types involved in the skin recovery process.…”
Section: Engineered Scaffolds For Wound Healingmentioning
confidence: 99%
“…Up to now, numerous strategies have been implemented to fabricate wound healing scaffolds, such as extrusion, molding, freeze-drying, rapid prototyping, and electrospinning. From these, electrospinning technique remains one of the most used, due to its simplicity, cost efficiency, flexibility, and scalability [ 14 ].…”
Section: Introductionmentioning
confidence: 99%